2020
DOI: 10.21512/lc.v14i1.6272
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Balinese EFL Learners’ Prior Learning Experience and Present Proficiency

Abstract: The research tried to shed light on the relation of prior learning experience and motivation in shaping the learners’ proficiency. It investigated the importance of prior learning experience and the role of motivation in learning development. This needed to investigate further to find out how positive and negative prior learning experience with intrinsic and extrinsic motivation determined the way the students, value their phase of learning, and the relation with their present proficiency. From the empirical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Motivation is one crucial aspect that relates to the learners' attitude towards reaching his/her goal. It can drive the action/behavior that can be seen in the learners' performance and results in the learners' proficiency (Pratiwi, 2020).…”
Section: The Role Of Teachers In Motivating Students In Online Learningmentioning
confidence: 99%
“…Motivation is one crucial aspect that relates to the learners' attitude towards reaching his/her goal. It can drive the action/behavior that can be seen in the learners' performance and results in the learners' proficiency (Pratiwi, 2020).…”
Section: The Role Of Teachers In Motivating Students In Online Learningmentioning
confidence: 99%
“…It is also asserted by Wulyani et al, (2019) that self-motivation to keep learning is necessary for English teachers on an individual basis. Pratiwi (2020) reports in her study which involves fifteen English learners from Bali ranging from 19-23 years old that high intrinsic motivation motivates the English learners and contributes to higher English proficiency. However, low intrinsic motivation results in demotivation and lower English proficiency.…”
Section: Expose Myself To Lots Of English Learning Resources Because ...mentioning
confidence: 99%
“…Travelling to English speaking countries also gives students opportunity to build their confidence and enhance English proficiency as well. Nonetheless, a short time visit does not significantly develop English learners' proficiency (Pratiwi, 2020). It is found that consistent exposure and use of English really help to develop English proficiency gradually (Faez & Karas, 2019).…”
Section: Also Did Extensive Listening Because I Wanted To Improve My ...mentioning
confidence: 99%
See 2 more Smart Citations